2021
DOI: 10.22456/1679-9216.114452
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry, Topography and Arterial Supply of the Thyroid Gland in Brazilian Shorthair Cats

Abstract: Background: Thyroid gland diseases are the most common endocrinopathies in feline practice. Diagnosis and surgical treatment must base on solid anatomical knowledge about the gland size, localization, and blood supply. However, some textbooks provide a general anatomical description of the thyroid gland of domestic carnivores. Thus, specific details of the feline gland are missing. The present study aimed to investigate the dimensions, topography, and arterial supply of the thyroid gland in Brazilian shorthair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Limited data regarding the morphometry, topography, and vascularization of the thyroid gland in primates are available. This study found no differences between the left and right lobes of the thyroid gland in rhesus monkeys, consistent with previous studies on other mammal species such as Santa Inês sheep (Lima et al, 2009), domestic dogs (Rodrigues et al, 2016), and Brazilian Shorthair Cats (Stocco et al, 2021). However, Novo et al (2009) reported larger measurements for the left lobe than the right lobe in dogs using ultrasonographic examination.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Limited data regarding the morphometry, topography, and vascularization of the thyroid gland in primates are available. This study found no differences between the left and right lobes of the thyroid gland in rhesus monkeys, consistent with previous studies on other mammal species such as Santa Inês sheep (Lima et al, 2009), domestic dogs (Rodrigues et al, 2016), and Brazilian Shorthair Cats (Stocco et al, 2021). However, Novo et al (2009) reported larger measurements for the left lobe than the right lobe in dogs using ultrasonographic examination.…”
Section: Methodssupporting
confidence: 90%
“…The thyroid gland in rhesus monkeys was located ventrolateral to the trachea, similar to many other domestic and wild mammals (Akudu et al, 2018;Borges et al, 2019;Carvalho et al, 2003;König and Liebich, 2016;Policeni et al, 2012;Rodrigues et al, 2016;Silva et al, 2019;Stocco et al, 2021;Yamasaki, 1990Yamasaki, , 1996Yamasaki, , 2016. However, koalas arranged it laterally to the trachea at the clavicle level (Yamasaki, 1993).…”
Section: Topographymentioning
confidence: 60%
See 1 more Smart Citation